CARDIOPROTECTIVE EFFECT OF REMOTE ISCHEMIC PRECONDITIONING: FROM BENCH TO BEDSIDE - Suprayoga, Imam Mi'raj; Anjarwani, Setyasih (Universitas Brawijaya, 2024)
Remote ischemic preconditioning (rIPC) refers to a cardioprotective phenomenon in which short episodes of ischemia, followed by reperfusion, in one organ or tissue might provide future protection against ischemia/reperfusion damage in other organs, namely the heart. The process involves the activation of humoral, neural, or systemic communication channels, which in turn induce various intracellular signals inside the heart. The primary objective of this review is to provide a concise overview of the potential processes implicated in rIPC cardioprotection, as well as to elucidate current clinical studies aimed at establishing the effectiveness of these techniques in safeguarding the heart from detrimental ischemia/reperfusion injury. In this context, many variables contribute to the attenuation of subcellular processes of rIPC in patients, including advanced age, presence of comorbidities, medication use, and variations in anaesthetic protocols. These factors may account for the observed variability in outcomes across different clinical studies. Additional research, meticulously planned, is needed in order to enhance our comprehension of the pathways and mechanisms associated with both early and late rIPC. A comprehensive understanding of the various routes is crucial in facilitating the translation of medical advancements to the benefit of patients.